Meningkatkan Kemampuan Motorik Halus Anak Melalui Kegiatan Mencetak Menggunakan Media Bahan Alam Di Taman Kanak-kanak - Dina, Saputri; St. Maria , Ulfah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
The reality faced by group A Kindergarten Harapan Ibu is that the majority of students are not yet able to print with natural materials. It appears that children are still not able to print with natural materials that have been determined by the teacher. Often children have difficulty printing. Children in group A should be able to print using natural materials. Of the 11 students in group A, only 4 people (36.4%) were able to print with natural materials, the remaining 7 people (63.6%) were not able to make collages. From the implementation of learning improvements in activities to improve children's fine motor skills in Group A Mother's Expectations which were carried out in the second learning cycle, it can be concluded that: very significant final achievements were clearly visible in the first cycle, there were 3 children (27.3%) who were starting to develop, 8 children (72.7%) developed according to expectations. In cycle II, namely children's activities, in the collage making activity using the assignment method in cycle II there were 11 children (100%) who developed. As Expected.